Public perception of algorithmic policing in a non-democratic context: evidence from Kazakhstan. - Gritsenko, Daria; Trochev, Alexei; Vehkalahti, Kimmo (Policing & Society, 2025)
Governments around the world use advanced computer algorithms and data-driven systems to enhance their law enforcement systems. Research on public attitudes towards the use of such algorithmic policing in non-democratic countries remains scarce. Our study addresses this gap by exploring attitudinal factors influencing the acceptance of algorithmic policing in a non-democratic regime with a novel dataset from a survey conducted in Kazakhstan in May 2023 (N = 1748). Our findings contribute to the literature on algorithmic policing and authoritarian digitalisation, demonstrating how algorithmic tools become a part of the 'authoritarian bargain' to deliver governance efficiency without political reforms.